Multidimensional Mechanistic Spectrum of Long Non-coding RNAs in Heart Development and Disease - Han, Lei; Yang, Lei (Frontiers in Cardiovascular Medicine, 2021)
With the large-scale genome-wide sequencing, long non-coding RNAs (lncRNAs) have been found to compose of a large portion of the human transcriptome. Recent studies demonstrated the multidimensional functions of lncRNAs in heart development and disease. The subcellular localization of lncRNA is considered as a key factor that determines lncRNA function. Cytosolic lncRNAs mainly regulate mRNA stability, mRNA translation, miRNA processing and function, whereas nuclear lncRNAs epigenetically regulate chromatin remodeling, structure, and gene transcription. In this review, we summarize the molecular mechanisms of cytosolic and nuclear lncRNAs in heart development and disease separately, and emphasize the recent progress to dictate the crosstalk of cytosolic and nuclear lncRNAs in orchestrating the same biological process. Given the low evolutionary conservation of most lncRNAs, deeper understanding of human lncRNA will uncover a new layer of human regulatory mechanism underlying heart development and disease, and benefit the future clinical treatment for human heart disease.